DELSILIFE in the Philippines [videorecording] an educational strategy to fight poverty - Boeren, Ad JJM.; Center for the Study of Education in Developing Countries (CESO).; SEAMEO Regional Center for Educational Innovation and Technology (INNOTECH). (Quezon City CESO-INNOTECH, 1988)
DELSILIFE is a development project aimed towards alleviating poverty through education. The documentary focuses on Loma de Bato, Bulacan and Jehnoc, Iloilo - two communities which have been helped by the DELSILIFE learning program. DELSILIFE offers two major types of programs: The Livelihood Learning Program; and the Basic Life Skills program. The DELSILIFE education not only equipts the community members with skills but has also improved their attitudes.
Film was funded by the Netherlands Government.
VHS.
Narrator, Nicanor Arragon.
Keywords: Rural development projects -- Philippines; Rural development -- Philippines; DELSILIFE